Environmental & architectural phenomenology. Vol. 3, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1992)
Vol. 3, No. 2, Spring 1992 (includes book review of Paul Krapfel's Shifting, and essays by Joe Grange, Ralph Acampora & Ingrid Leman Stefanovic).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals